Nutritional Exchanges Within Tumor Microenvironment: Impact for Cancer Aggressiveness - Comito, Giuseppina; Ippolito, Luigi; Chiarugi, Paola; Cirri, Paolo (Frontiers in Oncology, 2020)
Neoplastic tissues are composed not only by tumor cells but also by several non-transformed stromal cells, such as cancer-associated fibroblasts, endothelial and immune cells, that actively participate to tumor progression. Starting from the very beginning of carcinogenesis, tumor cells, through the release of paracrine soluble factors and vesicles, i.e., exosomes, modify the behavior of the neighboring cells, so that they can give efficient support for cancer cell proliferation and spreading. A mandatory role in tumor progression has been recently acknowledged to metabolic deregulation. Beside undergoing a metabolic reprogramming coherent to their high proliferation rate, tumor cells also rewire the metabolic assets of their stromal cells, educating them to serve as nutrient donors. Hence, an alteration in the composition and in the flow rate of many nutrients within tumor microenvironment has been associated with malignancy progression. This review is focused on metabolic remodeling of the different cell populations within tumor microenvironment, dealing with reciprocal re-education through the symbiotic sharing of metabolites, behaving both as nutrients and as transcriptional regulators, describing their impact on tumor growth and metastasis.